Modern features of benchmarking in the hotel business - E. L. Zadneprovskaya; T. N. Poddubnaya; E. A. Panina; T. A. Dzhum (Новые технологии)
The market of hotel services is an actively developing market in which innovative technologies of service of guests are widely used; various loyalty and reservation programs are being developed and improved; new approaches to business process management are applied. Benchmarking is a very relevant area designed to assess and select alternative options for the development of the hotel business, defining tasks and improving management efficiency through a deeper study and borrowing approaches successfully implemented by competitors. The aim of the research is to study the current features of benchmarking in the hospitality industry and its impact on the dynamics of enterprise performance. The research methods used are method of competitive analysis, statistical method, generalization method, forecasting. The results and conclusions: the analysis of the state of the hotel services market has shown a steady growth in the number of facilities and consumers of hotel services, which leads to increased intra-industry competition. Benchmarking helps to correlate the operating performance of the hotel business with the performance of the competitive environment, to move away from the subjective assessments of hoteliers and to identify errors in sales policy. In addition, the use of benchmarking allows you to predict the dynamics of demand in order to minimize managerial errors. The conclusions: benchmarking is part of marketing research and the basis for business process planning in the context of choosing strategic activities of the hotel service company. Conducting such a study is focused on providing the hotel with significant competitive advantages, the quintessence of which is the procedure of studying the experience of operating in the market of business leaders.